LEGAL POLITICS OF EMPLOYMENT IN TERM OF PART OF TASK HANDOVER TO OTHER COMPANIES IN INDONESIA - Endah Pujiastuti (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The handover of part task to other companies is currently being practiced by the company in the context to efficiency and effectiveness. In the midst of the controversy of the practice in handover of part task to other companies, the government still does not remove the regulations that have been issued. Based on observation, the regulation of the handover of part task to another company has been very dinamic in five years last. The movement of this regulation is more directed at efforts to improve its implementation, especially for legal protection. These conditions are very different compared to previous years that seemed untouched. This paper discusses the legal politics of the labor, which focuses on the field of study of the handover of parttask to other companies in Indonesia. Keywords: task, company, handover, legal politics.